If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 1.5x + -4.8 Reorder the terms: 6 = -4.8 + 1.5x Solving 6 = -4.8 + 1.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5x' to each side of the equation. 6 + -1.5x = -4.8 + 1.5x + -1.5x Combine like terms: 1.5x + -1.5x = 0.0 6 + -1.5x = -4.8 + 0.0 6 + -1.5x = -4.8 Add '-6' to each side of the equation. 6 + -6 + -1.5x = -4.8 + -6 Combine like terms: 6 + -6 = 0 0 + -1.5x = -4.8 + -6 -1.5x = -4.8 + -6 Combine like terms: -4.8 + -6 = -10.8 -1.5x = -10.8 Divide each side by '-1.5'. x = 7.2 Simplifying x = 7.2
| (5i)(x^2)= | | C=48y+0.99nwhatsy | | -2x+5=14for(y) | | -4x^2=x-5 | | 2t-3r=9 | | 7+m=15 | | (x^2+2x+1)(x-2+5i)= | | 7+j=15 | | 5a*2=100 | | -2(2x-3)+8x=-6(x+1) | | 5a+730=100 | | 2+6-1=x+16-4 | | y=1.5(20)-4.8 | | -19+12=5(n+-4)-4 | | y-9+4y+6=12 | | 2/3(3)+4=3/5(3)-2 | | 5-6b-2-9=-6-6b | | 2(x+6)=6x-4 | | 6[2y-3(2y-3)]=12 | | (x+1)(x+1)(x-2+5i)= | | -6xy(4x+y)= | | 4a^2+5=12a | | 3(n-6)-5m=-24 | | 6(2y-3)=10 | | -19+12=5(n-4)-4 | | -9(-5-2x)+2-(-x-8)=-x(3-4)+2(x-3)-7 | | 8*c=24+2*c | | 3xs= | | 5a+2=100 | | 6-n=4+5n | | Ln(-r+10)=ln(r+10) | | 2(13x)+1(4)=95(26x)-1(3) |